Menata Ruang, Membuka Akses: Analisis Ergonomi Pembelajaran Motorik Anak Usia Dini Dalam Perspektif Universal Design For Learning - Hayati, Miratul (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2026)
Early childhood motor development learning requires a physical environment that ensures bodily comfort, safety, and equitable access for all children. This study aims to analyze the arrangement of learning spaces for early childhood motor development from the perspectives of ergonomics and Universal Design for Learning (UDL). A qualitative approach was employed through a literature review and conceptual analysis of ergonomic furniture practices, children’s body posture, and the flexibility of learning spaces. The analysis shows that the use of furniture suited to children’s body sizes, supportive working postures, and flexible spatial layouts play an important role in facilitating fine motor activities. Comfortable physical conditions help children maintain focus and hand‑movement control when performing manipulative tasks. The UDL perspective strengthens these findings by emphasizing the provision of choices in positions, tools, and ways of engaging in activities based on the diversity of children’s motor abilities. Therefore, ergonomic and inclusive learning space design is a fundamental foundation for supporting optimal and equitable fine motor development in early childhood.